Hypoxia exacerbates heat stress effects on the porcine intestinal epithelium in vitro - Pearce, S. C.; Gabler, N. K. (Frontiers in Animal Science, 2023)
Heat stress (HS) negatively impacts human health, as well as animal agriculture. Our objective was to tease out the effects of HS alone, and hypoxia alone while also examining the compound effects of a two-stressor system. The mechanisms underlying heat stressHS-induced intestinal dysfunction in vivo are still not fully elucidated. However, heat stressHS has been shown to cause intestinal ischemia/hypoxia which contributes to reduced barrier integrity. The objective of this study was to examine hypoxia alone, HS alone, as well as a combination using IPEC-J2 cells. Thus, weWe hypothesized that hypoxia is a critical factor and important step in the pathway to HS-induced barrier dysfunction. Porcine IPEC-J2 cells were grown in Transwell™ plates and then treated either under thermal neutral (TN; 38°C) or heat stress (HS; 42°C) and either normoxia (NX; ~21% O2) or hypoxia (HX; 1% O2) for 24 h. Transepithelial electrical resistance, paracellular permeability marker, FITC-Dextran, media interleukin 8, cell HSP70 and 90, as well as CLDN4, ZO-1 and EEA1 were all analyzed. Results showed that HS did not causenot increase intestinal permeability in this model, elicited a reduction in IL-8 while still exhibiting a robust HSP response. In this model, hHypoxia was required to induce intestinal barrier dysfunction and TJ re-distribution. The combination of HS and hypoxia caused even